2018
DOI: 10.20870/oeno-one.2018.52.1.2119
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of Tempranillo and Cabernet-Sauvignon varieties cultivated in the Ribera del Duero DO: observed variability and predictions under climate change scenarios

Abstract: Aim: This research examined relationships between grapevine phenology and climate in the Ribera del Duero DO (Spain). The observed varieties included Tempranillo, the main variety planted in the region, and Cabernet-Sauvignon.Methods and Results: Phenological events for stages C (budbreak), I (bloom), M (véraison) and N (maturity) were analyzed for 2004-2015. Dormant period chilling and late winter heating requirements to initiate growth were evaluated and accumulated temperature (growing degree days-GDD) prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
(55 reference statements)
3
22
0
Order By: Relevance
“…Hence, the GDD linear model is not always the best approach to model and simulate grapevine phenology, as the phenology-temperature relationship may be of non-linear nature. The present study results are comparable, in terms of model performance, to other studies in other winemaking regions worldwide [19,26,27,43,[62][63][64][65]. Although the aforementioned models provide the best approaches, it is important to bear in mind that they are bound to this particular phenology dataset.…”
Section: Discussionsupporting
confidence: 81%
“…Hence, the GDD linear model is not always the best approach to model and simulate grapevine phenology, as the phenology-temperature relationship may be of non-linear nature. The present study results are comparable, in terms of model performance, to other studies in other winemaking regions worldwide [19,26,27,43,[62][63][64][65]. Although the aforementioned models provide the best approaches, it is important to bear in mind that they are bound to this particular phenology dataset.…”
Section: Discussionsupporting
confidence: 81%
“…For this period, the values of GDD ranged between 1,473 and 1,547°C which were similar to those reported for other red cultivars. In this regard, Verdugo-Vásquez et al (2016) reported a range between 1,455 and 1,640°C for Cabernet Sauvignon while Ramos et al (2018) indicated 1,358 and 1,483°C for cvs. Cabernet Sauvignon and Tempranillo, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…The period between BB and BL may be shortened by up to 4.8 and 7.5 days by 2070, the period from BL to V could be shortened by up to 7.5 and 8.5 days, while the period from V to M might be shortened by 5.4 and 8.1 days under the two emission trajectories (RCP4.5 and RCP8.5), respectively. These changes are similar to those projected for other red varieties cultivated in the same area, such as Tempranillo (Ramos et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%